Evaluating the Social and Economic Impact of Batik Industry Development in West Java: An SROI Approach - Dwi Rahmawati; Nancy Margried Panjaitan (Jurnal Manajemen dan Kewirausahaan, 2025)
Indonesia’s batik industry has seen fluctuating export trends, peaking at USD 744.79 million in 2022 before declining by 13.51% in 2023. To support batik artisans, Deposit Insurance Corporation is called Lembaga Penjamin Simpanan (LPS) in Indonesia and Batik Fractal launched a corporate social responsibility (CSR) initiative—an end-to-end business training program in Sukabumi and Cianjur, West Java. This study evaluates its impact using the Social Return on Investment (SROI) framework, which measures social, economic, and environmental benefits. The program improved artisans’ digital literacy with jBatik applications, enhanced design creativity, strengthened financial management, and optimized pricing strategies and social media use. The SROI ratio of 17.039 indicates that every Rp 1 invested generates Rp 17,039 in social impact, demonstrating the program’s efficiency. These findings emphasize the need for structured training, certification, and mentorship to preserve traditional batik techniques while fostering innovation. Market expansion through digital platforms, branding, and export assistance, along with financial support, can enhance industry sustainability. Furthermore, adopting technology, such as blockchain for authenticity verification and eco-friendly innovations, can modernize the sector. This study highlights the effectiveness of targeted interventions in strengthening economic resilience and safeguarding Indonesia’s cultural heritage.